Changes and challenges in museum management after the COVID-19 pandemic - Byungjin Choi; Junic Kim (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
To investigate how museums will change after the coronavirus disease 2019 (COVID-19) pandemic, and to seek opinions on how well they can secure sustainable competitiveness, this study conducted 15 in-depth interviews using snowball sampling. The interviewees consisted of: an artists' group, a museum-related group, and a users' group. Our findings revealed that museums are working hard to gain competitiveness in the face of COVID-19, for which they changed their existing business models to a great extent. One of the most significant changes they introduced, was considering their users as internal, rather than external, stakeholders. For promoting museum products, encouraging users to participate makes them strong supporters who are more active across online platforms and engage and motivate new users, thereby configuring the network effects. The study concludes that this innovative trend will contribute to museums' sustainable competitiveness during the pandemic as well as in the post-pandemic era.
Keywords: 650; value co-creation; connecting museums; pandemic; network effects; digitalisation